Discrimination in healthcare settings among adults with recent HIV diagnoses. Issue 9 (2nd September 2019) - Baugher, Amy R.; Beer, Linda; Fagan, Jennifer L.; Mattson, Christine L.; Shouse, R. Luke; ,
ABSTRACT: The prevalence of discrimination in healthcare settings among HIV patients in the United States is unknown. The Medical Monitoring Project (MMP) is a complex sample survey of adults receiving HIV medical care in the United States. We analyzed nationally representative MMP data collected 2011–2015. We assessed the prevalence of self-reported healthcare discrimination, perceived reasons for discrimination, and factors associated with discrimination among persons with HIV diagnoses ≤5 years before interview ( n  = 3, 770). Overall, 14.1% of patients living with HIV (PLWH) experienced discrimination, of whom 82.2% attributed the discrimination to HIV. PLWH reporting poverty, homelessness, or attending a non-Ryan White HIV/AIDS Program (RWHAP) facility were more likely to report discrimination compared with other groups. Of patients attending non-RWHAP facilities, discrimination was higher among those in poverty (27.5%) vs. not in poverty (15.1%). Discrimination was associated with homelessness regardless of facility type, and was highest among homeless persons attending non-RWHAP facilities. Healthcare discrimination was commonly reported among PLWH, and was most often attributed to HIV status. Discrimination was higher among those reporting poverty or homelessness, particularly those attending non-RWHAP facilities. Incorporating practices, such as anti-discrimination training, in facilities may reduce healthcare discrimination.